Smartphone-Based Microphone: A Multi-User Service for Collaborative Work - Anastasia A. Firsova; Dmitry G. Korzun (Proceedings of the XXth Conference of Open Innovations Association FRUCT, 2016)

(untitled)
SmartRoom is a smart space-based system for assisting such collaboration activity as a conference or a meeting. The assistance is in the form of digital services provided to the users, having personal mobile devices (e.g., smartphone), in a multimedia-equipped room. In this work, we continue our development of microphone service, which allows a SmartRoom user to exploit her/his smartphone as a microphone wirelessly linked with an audio system in the room. The service supports new scenarios for voice communication between a current speaker and other participants. In the considered case study, the client part is implemented for Android mobile devices.